Characterization and in vitro release studies of oral microbeads containing thiolated pectin-doxorubicin conjugates for colorectal cancer treatment - Cheewatanakornkool, K.; Niratisai, S.; Manchun, S.; Dass, Crispin; Sriamornsak, P. (2017)
© 2017 Shenyang Pharmaceutical University. Novel oral microbeads were developed based on a biopolymer-drug conjugate of doxorubicin (DOX) conjugated with thiolated pectin via reducible disulfide bonds. The microbeads were fabricated by ionotropic gelation with cations such as Al 3+ , Ca 2+ and Zn 2+ . The results showed that using zinc acetate can produce the strongest microbeads with spherical shape. However, the microbeads prepared from thiolated pectin-DOX conjugate were very soft and irregular in shape. To produce more spherical microbeads with suitable strength, the native pectin was then added to the formulations. The particle size of the microbeads ranged from 0.87 to 1.14 mm. The morphology of the microbeads was characterized by optical and scanning electron microscopy. DOX was still in crystalline form when used in preparing the microbeads, as confirmed by powder X-ray diffractometry. Drug release profiles showed that the microbeads containing thiolated pectin-DOX conjugate exhibited reduction-responsive character; in reducing environments, the thiolated pectin-DOX conjugate could uncouple resulting from a cleavage of the disulfide linkers and consequently release the DOX. The best-fit release kinetics of the microbeads containing thiolated pectin-DOX conjugate, in the medium without reducing agent, fit the Korsmeyer-Peppas model while those in the medium with reducing agent fit a zero-order release model. These results suggested that the microbeads containing thiolated pectin-DOX conjugate may be a promising platform for cancer-targeted delivery of DOX, exploiting the reducing environment typically found in tumors.